La gravedad de la infección por el virus respiratorio sincicial (VRS) y la participación del polimorfismo -2871 A>G del gen TLR-9 en lactantes chilenos menores de 6 meses de edad - Silva M., Jorge; Castillo M., Carlos; Larrañaga L., Carmen; Ampuero Ll., Sandra (Revista Hospital Clínico Universidad de Chile, 2012)
Respiratory syncytial virus (RSV) is the most common cause of severe lower respiratory tract infection (LRTI) in infants. In Chile, 2% of children infected with RSV are hospitalized. Nowadays, genetic factors as Single Nucleotide Polymorphisms (SNPs) in innate immune genes have been associated with the RSV infection severity. We studied the association between the SNP-2871 A>G (rs187084) in TLR9 gene and severity of infection in Chilean infants. Ninety seven, previously healthy term infants (< 6-months) with RSV-LRTI were analyzed. The severity of disease was determined by clinical scoring system. RSV and other respiratory virus were confirmed by immunofluorescence assays and, or reverse transcription-real time PCR in nasopharyngeal aspirate sample. SNP was analyzed by PCR and RFLP in blood sample. Unphased program and Armitage’s test were used for genetic analysis. Infants were grouped in mild (n:31), moderate (n:28) and severe (n:38). There were no differences in sex or age between RSV groups. For all infants, the frequency for allele A was 0.639. Genotypic frequencies were 40.2% A/A; 47.4% A/G and 12.4% G/G. There were not statistical differences between infant groups. The SNP -2871 A>G in TLR9 is not associated to severity RSV infection in Chilean infants.